2020
DOI: 10.3390/ijerph17072191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Work–Family Conflict, Job Stress and Job Satisfaction on Seafarer Performance

Abstract: A lack of research has been undertaken to explore work–family conflict and its impact on the shipping industry. The objective of the present study was to empirically examine the effects of work–family conflict, job stress, and job satisfaction on seafarer performance. Data were collected from merchant ship seafarers in the Yangshan Port, Shanghai, China (n = 337). A data analysis was performed using hierarchical regression analysis. The research results revealed that work–family conflict and job stress negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 74 publications
4
33
0
1
Order By: Relevance
“…This study indicated that WFC negatively impacts job satisfaction and job performance. This conclusion is consistent with the conclusion of An et al [ 48 ] that WFC is negatively related to job outcomes in a Chinese project context. Nevertheless, this result is different from that of Allen et al [ 49 ], who found that WFC does not have a significant relationship with job outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study indicated that WFC negatively impacts job satisfaction and job performance. This conclusion is consistent with the conclusion of An et al [ 48 ] that WFC is negatively related to job outcomes in a Chinese project context. Nevertheless, this result is different from that of Allen et al [ 49 ], who found that WFC does not have a significant relationship with job outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…The items used to measure affective commitment were designed with reference to the relevant literature (Kaur and Mittal [ 12 ]; Ribeiro et al [ 26 ]; Odoardi et al [ 27 ]). The items applied to measure job satisfaction were designed according to previous studies (Cao et al [ 1 ]; Witt and Wilson [ 34 ]; An et al [ 48 ]). The items used to measure job performance were designed with reference to the relevant literature (Cao et al [ 1 ]; Saetang et al [ 28 ]; Xiong et al [ 29 ]).…”
Section: Variable Measurement and Pilot Testmentioning
confidence: 99%
“…The results show that work-to-family conflict negatively affects project success. This finding is consistent with the finding of An et al [84] and Hao et al [85], who found a significant negative relationship between work-to-family conflict and job outcomes in China. However, this finding is inconsistent with the conclusion of Allen et al [86], who found no significant relationship between work-to-family conflict and job outcome in America.…”
Section: Effects Of Work-to-family Conflict On Project Successsupporting
confidence: 93%
“…Seafarers are an occupational group with one of the highest risks of stress [ 1 ]. Seafarers have to endure separation from family, burnout, time pressure, dealing with checks, workplace noise, sleep deprivation, cross-cultural communication, recreation scarcity, interpersonal stress, physiological needs, and heat due to job demands [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have been conducted with a focus on formulating strategies to retain seafarers. Most studies highlight the importance of improving mental health, physical health, well-being, job satisfaction, and stress relief, to retain seafarers [ 7 , 15 , 16 ]. However, little is known about the factors positively influencing turnover intention.…”
Section: Introductionmentioning
confidence: 99%